Essential Oil Composition of Baccharis tenella Hook. Et Arn. - Biurrun, Fernando (2005)
The essential oils of Baccharis tenella Hook et al Arn. leaves collected form Llanos Region (La Rioja) was analyzed by GC and GCMS. Spathulenol was major component of essential oils (29.4%)